The β isoform of the catalytic subunit of protein phosphatase 2B restrains platelet function by suppressing outside‐in αIIbβ3 integrin signaling. (15th November 2014) - Khatlani, T.; Pradhan, S.; Da, Q.; Gushiken, F. C.; Bergeron, A. L.; Langlois, K. W.; Molkentin, J. D.; Rumbaut, R. E.; Vijayan, K. V.
Summary Background Calcium‐dependent signaling mechanisms play a critical role in platelet activation. Unlike calcium‐activated protease and kinase, the contribution of calcium‐activated protein serine/threonine phosphatase in platelet activation is poorly understood. Objective To assess the role of catalytic subunit of protein phosphatase 2B (PP2B) or calcineurin in platelet function. Results Here, we showed that an increase in PP2B activity was associated with agonist‐induced activation of human and murine platelets. Pharmacological inhibitors of the catalytic subunit of protein phosphatase 2B (PP2B‐A) such as cyclosporine A or tacrolimus (FK506) potentiated aggregation of human platelets. Murine platelets lacking the β isoform of PP2B‐A (PP2B‐Aβ−/−) displayed increased aggregation with low doses of agonist concentrations. Loss of PP2B‐Aβ did not affect agonist‐induced integrin αIIbβ3 inside‐out signaling, but increased basal Src activation and outside‐in αIIbβ3 signaling to p38 mitogen‐activated protein kinase (MAPK), with a concomitant enhancement in platelet spreading on immobilized fibrinogen and greater fibrin clot retraction. Fibrinogen‐induced increased p38 activation in PP2B‐Aβ−/− platelets were blocked by Src inhibitor. Both PP2B‐Aβ−/− platelets and PP2B‐Aβ‐depleted human embryonal kidney 293 αIIbβ3 cells displayed increased adhesion to immobilized fibrinogen. Filamin A, an actin crosslinking phosphoprotein that is known to associate with β3, was dephosphorylated on Ser2152 in fibrinogen‐adhered wild‐type but not in PP2B‐Aβ−/− platelets. In a FeCl3 injury thrombosis model, PP2B‐Aβ−/− mice showed decreased time to occlusion in the carotid artery. Conclusion These observations indicate that PP2B‐Aβ by suppressing outside‐in αIIbβ3 integrin signaling limits platelet response to vascular injury.